The Analysis of the Chlorogenic Acid in the Ethanol Fraction of Robusta Coffee Beans and Its Effect on Glucose Levels in Wistar Rats - Rusman Hasanuddin; Jasmiadi Jasmiadi; Nurliana Abdillah (Disease Prevention and Public Health Journal, 2021)
Background: The metabolic disorder caused by high blood glucose levels and pancreatic beta-cell damage is known as diabetes mellitus. Indonesia itself is the 7th country in the world with the number of people with diabetes mellitus. Indonesia occupies rank 7 in the world with the number of people with diabetes mellitus. Apart from that, robusta coffee (Coffea canephora L) is one of the most popular drinks globally, including Indonesia. Chlorogenic acid in coffee beans effectively reduces cell damage due to free radicals, including minimizing excessive glucose release from the liver into the blood. Objective: This study aimed to analyze the effects of chlorogenic acid in the ethanolic fraction of robusta coffee (Coffea canephora L) beans on blood glucose levels in Wistar rats. Method: The researchers applied an experimental study with a randomized pretest-posttest control group design. The beans of robusta coffee were extracted using the Maceration method and then fractionated using a hexane and ethyl acetate solvent. The concentration of the obtained remaining fraction was measured using a spectrophotometer. Furthermore, hyperglycemia testing included 30 Wistar rats induced with 20% glucose for 3 – 4 weeks. They were then given the ethanol fraction of robusta coffee with a dose of 400 mg/kg BW and 500 mg/kg BW. Meanwhile, metformin served as a positive control, and NaCMC served as a negative control. Results: The chlorogenic acid analysis in the ethanol fraction of robusta coffee on a spectrophotometer with a concentration of 37% indicated a decrease of 16.66% on the negative control and 48.06% on the positive control. Meanwhile, the ethanol fraction of each control was 51.53% and 52.16%, respectively. Conclusion: The ethanol fraction of the robusta coffee significantly affects the decrease in blood glucose levels in Wistar rats.